Possible Directions for Computer Science Curriculum Development in the Future - Shoaib Khan; Abbas Afridi (Spectrum of Engineering Sciences, 2023)
In recent years, there has been increasing scrutiny and criticism over the traditional balance between research and education, as well as the public's funding for universities. Currently, numerous industrial and scientific sectors anticipate a continuous scarcity of highly skilled computer scientists and engineers. This is because contemporary society is progressively relying more on digital technologies. Compared to many other academic disciplines, the gap between the fundamental principles of computing and the cutting-edge advancements in research and practical applications is rather small in the field of computing. As a result, the curriculum for computer science and engineering (CS&E) must continuously adapt to include new and important advancements. Moreover, swift advancements in technology impact the delivery of education. Advancements in networking and graphics have enabled the creation and distribution of instructional resources that offer significant advantages to a wide audience. Keywords- Possible Directions, Computer Science, Curriculum Development